2021
DOI: 10.1038/s41467-021-23902-6
|View full text |Cite
|
Sign up to set email alerts
|

iPLA2β-mediated lipid detoxification controls p53-driven ferroptosis independent of GPX4

Abstract: Here, we identify iPLA2β as a critical regulator for p53-driven ferroptosis upon reactive oxygen species (ROS)-induced stress. The calcium-independent phospholipase iPLA2β is known to cleave acyl tails from the glycerol backbone of lipids and release oxidized fatty acids from phospholipids. We found that iPLA2β-mediated detoxification of peroxidized lipids is sufficient to suppress p53-driven ferroptosis upon ROS-induced stress, even in GPX4-null cells. Moreover, iPLA2β is overexpressed in human cancers; inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(145 citation statements)
references
References 43 publications
4
141
0
Order By: Relevance
“…The calcium-independent phospholipase iPLA2β was also recently shown to critically regulate p53-dependent ferroptosis upon reactive oxygen species (ROS)-induced stress, a classic regulator of cellular functions [ 39 41 ]. Peroxidized lipids detoxification mediated by iPLA2β is sufficient to suppress p53-driven ferroptosis, while iPLA2β inhibition sensitizes tumour cells to p53-driven ferroptosis, promoting p53-dependent tumour suppression in xenograft mouse models [ 42 ].…”
Section: P53 In Ferroptotic Cell Deathmentioning
confidence: 99%
“…The calcium-independent phospholipase iPLA2β was also recently shown to critically regulate p53-dependent ferroptosis upon reactive oxygen species (ROS)-induced stress, a classic regulator of cellular functions [ 39 41 ]. Peroxidized lipids detoxification mediated by iPLA2β is sufficient to suppress p53-driven ferroptosis, while iPLA2β inhibition sensitizes tumour cells to p53-driven ferroptosis, promoting p53-dependent tumour suppression in xenograft mouse models [ 42 ].…”
Section: P53 In Ferroptotic Cell Deathmentioning
confidence: 99%
“…The TP53 gene is an essential tumor suppressor gene for humans. It is generally believed that p53-mediated cell cycle arrest, apoptosis, and senescence are the major causes explaining tumor suppression ( 66 ). However, it remains unclear with regard to the mechanism of TP53 gene in ferroptosis.…”
Section: Molecular Mechanisms Of Cell Ferroptosismentioning
confidence: 99%
“…The latest research provides more possibilities that targeting ferroptosis may be a new strategy for tumor treatment. For example, Mao et al identified a ferroptosis-defensive mechanism mediated by Dihydroorotate dehydrogenase (DHODH) in the mitochondria, which works with mitochondrial glutathione peroxidase 4 (GPX4) to reduce ubiquinone to panthenol, thereby inhibiting ferroptosis in mitochondrial inner membrane, while Brequinar (a DHODH inhibitor) selectively inhibits the proliferation of tumor cells with low GPX4 expression by inducing ferroptosis, thus it can occur synergistically to induce ferroptosis and inhibit the growth of tumor cells with high GPX4 expression by the combined use of Brequinar and sulfasalazine (ferroptosis inducers) (127); Subsequently, Ding et al demonstrated that DMOCPTL induced ferroptosis and apoptosis primarily through GPX4 ubiquitination in triple-negative breast cancer cells (128); Additionally, D. Chen et al confirmed that IPLA2b inhibited ferroptosis by cleaving through lipid peroxide for detoxify without depending on GPX4, and that the absence of iPLA2b had no significant effect on the normal development or cell viability of normal tissues, thus, iPLA2b may become a new target for ferroptosis-targeted therapy for tumor (129); Furthermore, X. Wang et al demonstrated that SOX2 promoted SLC7A11 transcription by binding to SLC7A11 promoter, and oxidation at Cys265 of SOX2 inhibited its activity and decreased the self-renewal capacity of lung cancer stem cell-like cells. This suggests that oxidation of SOX2 could be a potential target for ferroptosis-targeted treatment for cancer (130).…”
Section: Iron and Ferroptosismentioning
confidence: 99%